2022
DOI: 10.3389/fphys.2022.917579
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Intestinal Homeostasis in Diarrhea-Predominant Irritable Bowel Syndrome by Electroacupuncture Through Submucosal Enteric Glial Cell-Derived S-Nitrosoglutathione

Abstract: Objective: To determine whether electroacupuncture (EA) maintains intestinal homeostasis in diarrhea-predominant irritable bowel syndrome (IBS-D) rats by repairing intestinal barrier function through enteric glial cell (EGC)-derived S-nitrosoglutathione (GSNO).Methods: Sprague–Dawley rats were randomly divided into a control group (n = 10) and an IBS-D group (n = 20). These rats received senna solution by gavage and chronic unpredictable mild stress for 14 days and were further divided into a model group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Enteric glial cells (EGCs) are widely available in the ENS [ 13 ] and play important roles in neuronal support, neuroprotection, neurogenesis, neuroimmune interaction, and synaptic transmission [ 14 ]. Previous investigations demonstrated that abnormal EGC activity is correlated with developing some intestinal diseases and their symptoms, such as chronic diarrhea, abdominal pain, bloating, and indigestion [ 15 ]. Furthermore, accumulating data indicates the importance of EGCs sustaining IEB [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enteric glial cells (EGCs) are widely available in the ENS [ 13 ] and play important roles in neuronal support, neuroprotection, neurogenesis, neuroimmune interaction, and synaptic transmission [ 14 ]. Previous investigations demonstrated that abnormal EGC activity is correlated with developing some intestinal diseases and their symptoms, such as chronic diarrhea, abdominal pain, bloating, and indigestion [ 15 ]. Furthermore, accumulating data indicates the importance of EGCs sustaining IEB [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%